North American validation of the Bokutoh criteria for withholding professional resuscitation in non-traumatic out-of-hospital cardiac arrest. (February 2019) - Grunau, Brian; Scheuermeyer, Frank; Kawano, Takahisa; Helmer, Jennie S.; Gu, Bobby; Haig, Scott; Christenson, Jim
Abstract: Background: Certain subgroups of patients with out-of-hospital cardiac arrest (OHCA) may not benefit from treatment. Early identification of this cohort in the prehospital (EMS) setting prior to any resuscitative efforts would prevent futile medical therapy and more appropriately allocate EMS and hospital resources. We sought to validate a clinical criteria from Bokutoh, Japan that identified a subgroup of OHCAs for whom withholding resuscitation may be appropriate. Methods: We performed a secondary analysis of the "Trial of Continuous or Interrupted Chest Compressions during CPR", which enrolled EMS-treated adult non-traumatic OHCA. We classified patients as per the Bokutoh criteria ("Bokutoh Positive": age ≥ 73, unwitnessed arrest, non-shockable initial rhythm) and calculated test performance for the primary outcome of favourable neurologic outcome (mRS ≤ 3) at hospital discharge. We calculated the number of EMS-hours and hospital days per patient with a favourable neurologic outcome. Results: Of 26, 148 patients in the parent trial, 5442 (21%) were "Bokutoh Positive", among whom 0.51% (95% CI 0.35– 0.75%) had favourable neurologic outcomes, and 1.2% (95% CI 0.92–1.5%) survived. The positive predictive value was 0.995 (95% CI 0.992–0.997). EMS and hospital-based resource utilization per favourable neurological outcome was 91 h and 199 days for in the "Bokutok Positive" group, respectively, and 5.7 h and 33 hospital days in the "Bokutok Negative" group. Conclusion: In this validation of the Bokutoh criteria in a large North American cohort of OHCA patients, 0.51% meeting criteria had favourable neurological outcomes. This may rapidly and reliably identify the one-fifth of OHCA who are very unlikely to benefit from resuscitation.